2D and Quasi‐2D Halide Perovskites: Applications and Progress. Issue 2 (6th November 2019) - Kim, Hyojung; Huynh, Kim Anh; Kim, Soo Young; Le, Quyet Van; Jang, Ho Won
Abstract : Two‐dimensional (2D) and quasi‐2D (q‐2D) halide perovskites (HPs) offer a number of advantages compared with their three‐dimensional (3D) counterparts for electronic and optoelectronic applications due to their tunable properties and superior stability. This mini‐Review, at first is focused on the atomic structure and the optical and electrical properties of 2D and q‐2D HPs. The unique properties of 2D HPs are addressed in comparison with 3D HPs. Recent progress in applications using 2D and q‐2D HPs is summarized, such as in solar cells, light‐emitting diodes, photodetectors, resistive random access memories, and artificial synapses. The main parameters that regulate the device performance and strategies for improving materials properties and device performance for each application are addressed. Finally, the perspective for the future development of 2D and q‐2D HPs is discussed. Abstract : Two‐dimensional (2D) and quasi‐2D halide perovskites (HPs) offer a number of advantages for electronic and optoelectronic applications. Herein, the atomic structure and the optical and electrical properties of 2D and quasi‐2D HPs, compared with 3D HPs, are focused upon. Then, recent progress in applications such as solar cells, light‐emitting diodes, photodetectors, resistive random access memories, and artificial synapses are summarized.